Evaluation of brain targeting efficiency of intranasal microemulsion containing olanzapine: pharmacodynamic and pharmacokinetic consideration. (2nd January 2016) - Patel, Rashmin B.; Patel, Mrunali R.; Bhatt, Kashyap K.; Patel, Bharat G.; Gaikwad, Rajiv V.
Abstract: The objective of this study was to develop and evaluate olanzapine (OZP) -loaded microemulsions (OZPME) for intranasal delivery in the treatment of schizophrenia. The OZPME was formulated by the spontaneous microemulsification method and characterized for physicochemical parameters. Pharmacodynamic assessments (apomorphine – induced compulsive behavior and spontaneous locomotor activity) were performed using mice. All formulations were radiolabeled with technetium-99 ( 99m Tc), and biodistribution of drug in the brain was investigated using Swiss albino rats. Brain scintigraphy imaging in rabbits was performed to determine the uptake of the OZP into the brain. OZPME were found clear and stable with average globule size of 23.87 ± 1.07 nm. In pharmacodynamic assessments, significant ( p < 0.05) difference in parameters estimated were found between the treated and control groups. 99m Tc-labeled OZP solution (OZPS)/OZPME/OZP mucoadhesive microemulsion (OZPMME) were found to be stable and suitable for in vivo studies. Brain/blood ratio at all sampling points up to 8 h following intranasal administration of OZPMME compared to intravenous OZPME was found to be five to six times higher signifying larger extent of distribution of the OZP in brain. Drug targeting efficiency and direct drug transport were found to be highest for intranasal OZPMME, compared to intravenous OZPME. Furthermore, rabbit brain scintigraphy also demonstrated higher intranasal uptake of the OZP into the brain. This investigation demonstrates a prompt and larger extent of transport of OZP into the brain through intranasal OZPMME, which may prove beneficial for treatment of schizophrenia.